Experimental considerations for the assessment of in vivo and in vitro opioid pharmacology - Hill, Rob (Pharmacol Ther, 2022)
Morphine and other mu-opioid receptor (MOR) agonists remain the mainstay treatment of acute and prolonged pain states worldwide. The major limiting factor for continued use of these current opioids is the high incidence of side effects that result in loss of life and loss of quality of life. The development of novel opioids bereft, or much less potent, at inducing these side effects remains an intensive area of research, with multiple pharmacological strategies being explored. However, as with many G protein-coupled receptors (GPCRs), translation of promising candidates from in vitro characterisation to successful clinical candidates still represents a major challenge and attrition point. This review summarises the preclinical animal models used to evaluate the key opioid-induced behaviours of antinociception, respiratory depression, constipation and opioid-induced hyperalgesia and tolerance. We highlight the influence of distinct variables in the experimental protocols, as well as the potential implications for differences in receptor reserve in each system. Finally, we discuss how methods to assess opioid action in vivo and in vitro relate to each other in the context of bridging the translational gap in opioid drug discovery.